Menopausal Status and Abdominal Obesity Are Significant Determinants of Hepatic Lipid Metabolism in Women. Issue 10 (October 2015) - Hodson, Leanne; Banerjee, Rajarshi; Rial, Belén; Arlt, Wiebke; Adiels, Martin; Boren, Jan; Marinou, Kyriakoula; Fisher, Ciaran; Mostad, Ingrid L.; Stratton, Irene M.; Barrett, P. Hugh R.; Chan, Dick C.; et al.
Abstract : Background: Android fat distribution (abdominal obesity) is associated with insulin resistance, hepatic steatosis, and greater secretion of large very low‐density lipoprotein (VLDL) particles in men. Since abdominal obesity is becoming increasingly prevalent in women, we aimed to investigate the relationship between android fat and hepatic lipid metabolism in pre‐ and postmenopausal women. Methods and Results: We used a combination of stable isotope tracer techniques to investigate intrahepatic fatty acid synthesis and partitioning in 29 lean and 29 abdominally obese women (android fat/total fat 0.065 [0.02 to 0.08] and 0.095 [0.08 to 0.11], respectively). Thirty women were premenopausal aged 35 to 45 and they were matched for abdominal obesity with 28 postmenopausal women aged 55 to 65. As anticipated, abdominal obese women were more insulin resistant with enhanced hepatic secretion of large (404±30 versus 268±26 mg/kg lean mass, P <0.001) but not small VLDL (160±11 versus 142±13). However, postmenopausal status had a pronounced effect on the characteristics of small VLDL particles, which were considerably triglyceride‐enriched (production ratio of VLDL2 ‐ triglyceride:apolipoprotein B 30±5.3 versus 19±1.6, P <0.05). In contrast to postmenopausal women, there was a tight control of hepatic fatty acid metabolism and triglyceride production in premenopausal women, whereby oxidation ( r s =−0.49, P =0.006), de novo lipogenesis ( r s =0.55, P =0.003), and desaturation ( r s =0.48, P =0.012) were closely correlated with abdominal obesity‐driven large VLDL‐triglyceride secretion rate. Conclusions: In women, abdominal obesity is a major driver of hepatic large VLDL particle secretion, whereas postmenopausal status was characterized by increased small VLDL particle size. These data provide a mechanistic basis for the hyperlipidemia observed in postmenopausal obesity.